Deep Learning in Age-invariant Face Recognition: A Comparative Study. (5th December 2020) - Sajid, Muhammad; Ali, Nouman; Ratyal, Naeem Iqbal; Usman, Muhammad; Butt, Faisal Mehmood; Riaz, Imran; Musaddiq, Usman; Aziz Baig, Mirza Jabbar; Baig, Shahbaz; Ahmad Salaria, Umair
Abstract: This paper presents comparative evaluation of an application of deep convolutional neural networks (dCNNs) to age invariant face recognition. To this end, we use four distinct dCNN models, the AlexNet, VGGNet, GoogLeNet and ResNet. We assess their performance to recognize face images across aging variations, firstly by fine-tuning the models and secondly using them as face feature extractor. We also suggest a novel synthesized aging augmentation technique suitable for age-invariant face recognition using dCNNs. The face recognition experiments are conducted on three challenging FG-NET, MORPH and LAG aging datasets, and results are benchmarked with a simple CNN. The comparative study allows us to answer (i) when and why transfer learning or feature extraction strategies are useful in age-invariant face recognition scenarios, (ii) the potential of aging synthesized augmentation to increase accuracy and (iii) the choice of appropriate feature normalization and distance metrics to be used with deeply learned features. The extensive experiments, and valuable insights presented in this study can be extended to the design of effective age-invariant face recognition algorithms.